2017
DOI: 10.15835/nsb9310121
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Toxicity and Antifungal Activities of Megaphrynium macrostachyum (K. Schum) Leaf Extract against Foodborne Fungi

Abstract: This study aimed to examine the preservative potential of Megaphrynium macrostachyum on fungi responsible for the deterioration of orange juice and corn Jell-O. The phytochemicals from plants' leaves were extracted with four solvents: acetone, aqueous, ethanol and hexane. The solvents were differently and tested against fungi isolated from orange juice and corn Jell-O using disc diffusion method. Phytochemical screening of the extracts from the leaves was carried out, and the most active extract was tested via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…The phyto-constituents in M. macrostachyum leaf meal revealed that it contained the highest concentration of phenolic compound (1402 mg/g -1 ), followed by flavonoids (1205 mg/g -1 ), terpenoids (620 mg/g -1 ), tannins (318 mg/g -1 ), alkaloids (200 mg/g -1 ), steroids (51 mg/g -1 ), and glycosides. The phytochemical contents reported in this investigation are consistent with the findings of (Ibironke;Olusola, 2013;Adeogun et al, 2017). However, the amounts measured were higher than those reported by Adeogun et al (2017).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The phyto-constituents in M. macrostachyum leaf meal revealed that it contained the highest concentration of phenolic compound (1402 mg/g -1 ), followed by flavonoids (1205 mg/g -1 ), terpenoids (620 mg/g -1 ), tannins (318 mg/g -1 ), alkaloids (200 mg/g -1 ), steroids (51 mg/g -1 ), and glycosides. The phytochemical contents reported in this investigation are consistent with the findings of (Ibironke;Olusola, 2013;Adeogun et al, 2017). However, the amounts measured were higher than those reported by Adeogun et al (2017).…”
Section: Resultssupporting
confidence: 92%
“…The phytochemical contents reported in this investigation are consistent with the findings of (Ibironke;Olusola, 2013;Adeogun et al, 2017). However, the amounts measured were higher than those reported by Adeogun et al (2017). This suggests that factors such as plant age, geographical location, species, and processing method, among others, may alter phytoconstituents in plants (Ahmad et al, 2016;Alagbe, 2023).…”
Section: Resultssupporting
confidence: 90%